Práticas de alfabetização e letramento: uma experiência vivenciada no PIBID da UFPA - Campus Bragança - SILVA, Naara de Paula Ferreira da (2023)
The theme of this article is “School Management and Coordination: memory, internship and learning”. This is a qualitative work based on memory as a methodological resource of the supervised internship for the Degree in Pedagogy course, which was held at the Municipal School of Early Childhood Education Sagrado Coração de Jesus in the city of Viseu-Pa in 2017. The aim of this study is to make visible my experience in the Supervised Internship in Pedagogical Management and Coordination in Basic Education. The internship showed us how much the reality of the school context is totally different from what is studied in college. We created expectations of arriving in a school environment without difficulties. The manager has to go out of his way to seek improvements for the school and still be present on a daily basis, closely monitoring everything that happens at the school. The pedagogical coordinator assigns his/her role in early childhood education based on the articulation of good interpersonal relationships between those involved in the educational environment. In early childhood education, means must be created to make the pedagogical work dynamic and accessible to the students' reality. The internship was a useful experience, essential for our training. Through it, it was possible to experience the routine of school management and coordination, as the two functions are almost always confused by the similarities of activities, but it was necessary to make visible in the internship how the two functions complement each other and are fundamental for teaching and learning, especially in Child education.